Corporate Income Tax Rate and Foreign Direct Investment: A Cross-Country Empirical Study - Amalia Indah Sujarwati; Riatu Mariatul Qibthiyyah (Economics and Finance in Indonesia, 2020)
This study aims to explore the impact of Corporate Income Tax Rate (CITR) on Foreign Direct Investment (FDI), specified based on income levels of countries. Using an unbalanced fixed-effect method of 112 countries over the period of 2003–2017, our finding shows that CITR has no significant impact on FDI. Corporate Income Tax (CIT) is levied on all firms, and as CIT is generally more complex than other types of taxes, its influences on FDI are in question. Excluding tax havens from the sample, our findings show that CITR has a weak significance only in the lower-middle-income and low-income countries.